The Effect of Phosphorus Fertilization and Variety on The Growth and Production of Soybean (Glycine m a (L.) Merr) Under Saturated Soil Culture - Munif Ghulamahdi; Fred Rumawas; Joedojono Wiroatmodjo; Jajah Koswara (Forum Pasca Sarjana, 1991)
The objective of this expaiment was to study the effect of phosphorus fertilization on the growth and production of Americana and Lokon under saturated soil culture. The experiment was conducted at the Cikarawang Experimental Station, IPB, on a Latosol, from November 1988 until April 1989. Soybean yield did not respond to the phosphorus application, and maybe due to improved soil P availability under saturated condition. Leaf P concentrations at 9 weeks were sufficient (0.303 to 0.357%) for all levels of treatment. Active nodule growth was longer under saturated soil culture than conventional irrigation. Maximum active nodule growth under conventional culture was reached at 6 weeks, but under saturated soil culture was still increasing between 6 to 9 weeks from 0.175 to 0.342 g/plant for Americana and from 0.162 to 0.260 g/plant for Lokon. Increase of active nodule dry weight was followed by increase of leaf N concentration between 6 to 9 weeks from 3.366 to 3.674% for Americana, and from 3.382 to 3.695% for Lokon. Americana was more tolerant than Lokon to saturated soil culture. Number of Tied pods, 100- sads weight, and seed dry weight/plot of Americana were bigger than Lokon.